Targeting CD39 in combination with IL-2/anti-IL-2 complexes enhances cytotoxic immunity and limits tumor progression - Abrate, Carolina; Brunotto, Valentina; Bossio, Sabrina N.; Boccardo, Santiago; Tosello Boari, Jimena; Caudana, Pamela; Hernandez, Lara; Gimenez, Camila; Theumer, Martin G.; Sedlik, Christine; Amezcua-Vesely, Maria C.; Robson, Simon C.; et al. (Frontiers in Immunology, 2026)
Immunotherapies revolutionized cancer treatment, yet their efficacy remains constrained by the tumor’s immunosuppressive microenvironment. Here, we evaluated whether combining CD39 blockade with other modalities of immunotherapy such as IL-2/anti-IL-2 complexes (IL-2cx) administration could further enhance T cell-mediated antitumor responses and improve tumor control. We demonstrated that CD39 deficiency in MC38 tumor-bearing CD39KO (Entpd1 null) mice decreases tumor growth. This better tumor growth control was associated with increased infiltration of PD-1High CD8+ T cells, expressing elevated levels of exhaustion markers and transcription factors such as TOX. This PD-1High CD8+ T cell subset also exhibited a higher frequency of IFN-γ-producing and cytotoxic (Granzyme B+, Perforin+) cells. In contrast, the less immunogenic B16F10-OVA model did not show significant differences in tumor growth; however, CD39KO mice displayed an increased frequency of antigen-specific, pre-exhausted (PD-1Int) CD8+ T cells, a population recognized as a key target of immunotherapy. Pharmacological CD39 blockade with POM-1, when combined with IL-2cx treatment to redirect IL-2 activity, enhanced the accumulation of pre-exhausted CD8+ T cells with cytotoxic potential, thereby improving tumor control. This combinatorial strategy also reshaped the tumor immune landscape by increasing activated NK cells, elevating Granzyme B expression in CD4+ T cells, and decreasing immunosuppressive M-MDSCs expressing CD39, CD38, and CD73. Collectively, our findings demonstrate that integrating purinergic pathway inhibition with IL-2–based immunotherapies can coordinately reprogram lymphoid and myeloid compartments, attenuate immunosuppressive mechanisms within the tumor microenvironment, and amplify antitumor immunity, providing a strong rationale for advancing this strategy toward clinical translation.